Desain Emoticon dalam Komunikasi Interaktif - Mahatma Putri; Alvanov Zpalanzani Mansoor; Naomi Haswanto (Wimba : Jurnal Komunikasi Visual, 2011)
Internet becomes part of worldwide daily urban activities. Communication among people is intensified through various interfaces and media because of information technology convergence and the application of visual icons which represents emotion.The icons that represent emotions, expressions and feelings are titled emoticons. Emoticons are highly used in IT based communication gadgets such as portable PCs or cellulars. This paper develops and depicts the creation process, perception and cultural aspetcs that influenced the development of emoticon through visual communication design study theoretical and historical review.